Nested optimization design for combined cooling, heating, and power system coupled with solar and biomass energy - Zhang, Liang; Zhang, Lizhi; Sun, Bo; Zhang, Chenghui; Li, Fan (International journal of electrical power & energy systems, 2020)
•Combined cooling, heating, and power (CCHP) can improve energy efficiency.•Expanded with renewable energy, CCHP systems can provide a variety of benefits.•Optimization of such systems has neglected the variability of renewable resources.•We consider this variability to optimize the system capacity and operation.•Numerical results confirm energy, economic, and environmental benefits. Renewable energy source integration in combined cooling, heating, and power (RES-CCHP) systems can improve energy efficiency and foster renewable energy consumption, which is a promising solution to the current energy and environmental crisis. This paper studies the off-design characteristics of these systems, establishes a two-way interaction mechanism between the system capacity and operation strategy, and proposes a two-stage nested optimization design method for the RES-CCHP. In the first stage, the capacity of each system component is obtained by the genetic algorithm and then used as the constraint for the operation optimization. In the second stage, the nonlinear programming algorithm is employed to optimize the operational energy consumption, costs, and CO2 emissions taking the off-design characteristics of core devices into consideration. Several case studies are conducted to verify the feasibility of the two-stage optimal design method. It was found that the two-stage nested optimization design increases the primary energy saving ratio, cost saving ratio, and carbon dioxide emission reduction ratio by 4.5%, 4.32%, and 3.27% compared with the conventional optimal design method, respectively. Overall, the proposed two-stage nested optimization design was tested to improve the performance and the renewable energy consumption.